2022
DOI: 10.3390/plants11233232
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and Density of Gamma and X-ray Induced Mutations in a Non-Model Rice Cultivar

Abstract: Physical mutagens are a powerful tool used for genetic research and breeding for over eight decades. Yet, when compared to chemical mutagens, data sets on the effect of different mutagens and dosages on the spectrum and density of induced mutations remain lacking. To address this, we investigated the landscape of mutations induced by gamma and X-ray radiation in the most widely cultivated crop species: rice. A mutant population of a tropical upland rice, Oryza sativa L., was generated and propagated via self-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…3 illustrates examples of alleles displaying mutations in each mutant, focusing on chromosome 1, which exhibits the highest mutation incidence compared to other chromosomes. A similar incident also happened in the research of Jankowicz-Cieslak et al [30], where whole genome sequencing was used to detect the effects of mutations in rice. The results showed that eleven mutants had altered genomic composition.…”
Section: A Snp Analysismentioning
confidence: 70%
“…3 illustrates examples of alleles displaying mutations in each mutant, focusing on chromosome 1, which exhibits the highest mutation incidence compared to other chromosomes. A similar incident also happened in the research of Jankowicz-Cieslak et al [30], where whole genome sequencing was used to detect the effects of mutations in rice. The results showed that eleven mutants had altered genomic composition.…”
Section: A Snp Analysismentioning
confidence: 70%
“…Inducing mutations into genes with ionizing radiation is a well-known method of increasing genetic diversity in crop breeding. X-rays have proven effective in inducing phenotypic changes in many ornamental plant species, including achimenes, alstroemeria, azalea, begonia, bougainvillea, chrysanthemum, dahlia, carnation, hibiscus, lily, calla, rose, and tulip [11,[43][44][45][46][47][48][49][50]. However, the literature lacks studies on the effect of ionizing radiation on cacti.…”
Section: Discussionmentioning
confidence: 99%
“…Physical mutagens, such as gamma and X-rays, have been important mutagens for mutation breeding for over 80 years; however, the spectrum of mutations induced by these mutagens is not well understood. Jankowicz-Cieslak et al revealed the spectrum of mutations induced by gamma-and X-ray in rice using next-generation sequencing [14]. Hudson demonstrated that induced mutation by N-methyl nitrosourea (NMU) is an effective approach to improve protein and oil content in soybean [15].…”
mentioning
confidence: 99%